2006
DOI: 10.1096/fj.06-6228fje
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping Beauty‐based gene therapy with indoleamine 2,3‐dioxygenase inhibits lung allograft fibrosis

Abstract: Sleeping Beauty (SB) transposon is a natural nonviral gene transfer system that can mediate long-term transgene expression. Its potential utility in treating organ transplantation-associated long-term complications has not yet been explored. In the present study we generated an improved SB transposon encoding the human gene indoleamine-2,3-dioxygenase (hIDO), an enzyme that possesses both T cell-suppressive and antioxidant properties and selectively delivered the SB transposon in combination with a hyperactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 39 publications
(78 reference statements)
3
79
1
1
Order By: Relevance
“…The most direct evidence supporting the view about IDO as an immune-suppressive enzyme arises from transplant-related research. These studies consistently showed that enhanced IDO activity in donor organ/cells provides an efficient immunological shield to prevent a destructive allograft-reactive response without additional immunosuppressive treatments in a variety of animal models of organ/tissue transplantation, including heart (3), lung (4,5), liver (6), kidney (7), pancreas (8), skin (9), and bone marrow (10).…”
Section: Ndoleamine-23-dioxygenase (Ido)mentioning
confidence: 83%
See 1 more Smart Citation
“…The most direct evidence supporting the view about IDO as an immune-suppressive enzyme arises from transplant-related research. These studies consistently showed that enhanced IDO activity in donor organ/cells provides an efficient immunological shield to prevent a destructive allograft-reactive response without additional immunosuppressive treatments in a variety of animal models of organ/tissue transplantation, including heart (3), lung (4,5), liver (6), kidney (7), pancreas (8), skin (9), and bone marrow (10).…”
Section: Ndoleamine-23-dioxygenase (Ido)mentioning
confidence: 83%
“…The orthotopic left lung transplants were performed using Lewis donors and SpragueDawley recipient (allografts) or the same strain (isografts), as described previously (4,5,13). Some rats receiving allografts were given IDO inhibitor 1-mT in drinking water (5 mg/ml, pH 7) immediately after surgery.…”
Section: Animal Model In Vivo Gene Delivery Lung Function and Histomentioning
confidence: 99%
“…Color images available online at www.liebertonline.com/hum hypertension (L. Liu et al, 2006a). Furthermore, PEI-based systemic delivery of the SB transposon system encoding the human indoleamine-2,3-dioxygenase (hIDO) gene was evaluated in the context of lung transplantation-associated chronic complications, and found to elicit a remarkable therapeutic response, as evidenced by near normal pulmonary function in lung allografts (H. Liu et al, 2006). Last, SBmediated gene transfer significantly increased survival of mice bearing human glioblastoma xenografts by expressing antiangiogenic gene products (Ohlfest et al, 2005a), and improved the efficacy of immunotherapy by facilitating sustained cytokine expression after local, intratumoral injections of vector-PEI complexes (Wu et al, 2007).…”
Section: Fig 2 Expression Cassettes Delivered By Sleeping Beauty Trmentioning
confidence: 99%
“…Culture medium and total cell lysates from 24 independent clones were resuspended in 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) lysis buffer (20 mM HEPES, 0.5 M NaCl, 1 mM EDTA, 0.25% Triton X-100, 1 mM EGTA supplemented with a protease inhibitor cocktail) and screened for expression of IDO by western blotting and IDO activity assays. 46 As a negative control, cells transfected with the transposon pMSZ-CMV-GFP were used in place of the pMSZ-CMV-IDO and an identical selection process was carried out.…”
Section: Establishment Of Cell Lines Overexpressing Human Idomentioning
confidence: 99%